Self‐Locking in Systems of Multiple Bodies. Issue 1 (December 2014) - Brumme, Stephan; Tergeist, Mathias; Ostermeyer, G.‐P.
Abstract The phenomenon of self‐locking can be found in many technical applications and common machine parts, such as screws, chocks, and funnels. Despite this, research into this topic is mostly limited to specific applications (e.g., worm gears, screws, kinematic chains). Current works with a general scope are rare. This paper addresses the analysis of self‐locking in different, two‐dimensional, multibody systems, and shall contribute towards a more general analysis. To elaborate on the characteristics of self‐locking, the effect is first shown and explained using simple systems as examples. From these examples, an approach towards a generalized description of self‐locking is proposed, which is used as a foundation for the development of two identification methods. The analysis of the self‐locking mechanism in multibody systems is realized first through an analytical ansatz, and then using a numerical simulation of the examples shown. The analytical and numerical analyses of the systems deliver a criterion, and respectively an algorithm, which enables the identification of self‐locked assemblies in different systems of multiple bodies. The algorithm is designed to identify self‐locking during integration of the equations of motion, whereas the analytic criterion is formulated for static systems with known, increasing external loads. The results of the two analysis methods correspond very well for the given example systems, leading to the conclusion that both methods are equivalent and usable. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)